Psychosocial Needs and Their Relation to Achievement Motivation among Students at A'Sharqiyah University - Al-Ghefeili, Malak; Al-Lawati, Esam; Al-Wahaibi, Ibrahim (International Journal of Psychology, 2024)
Purpose: The current research underscores that university students are in a crucial stage of their development where their psychological and social needs play a pivotal role in their success in both academic and personal endeavours. The current research aims to know the contribution of psychological and social needs to the motivation of students at Al Sharqiyah University in the Sultanate of Oman to achieve their goals. Methodology: The study sample consisted of a total of (402) students enrolled in the university. In the current study, the researchers used two scales. The researchers prepared the first which was called the Psychological and Social Needs Scale. The researchers used the second scale, the Achievement Motivation Scale prepared by Safwat Kanaan (2003). Findings: The results of the first question indicated the existence of a positive relationship with statistical significance at a significance level of less than (0.05) between psychological and social needs and achievement motivation, and the value of the correlation coefficient reached (0.545). The results of the second question also indicated that the values ​​of the t-test for psychological and social needs were statistically significant at a significance level of (α≤0.05), which indicates that achievement motivation can be predicted through these needs. Therefore, through these results, achievement motivation can be predicted through psychological and social needs. Unique Contribution to Theory, Practice and Policy: It recommends the creation of counselling and educational programs designed to meet psychological and social needs effectively and the start of initiatives that enhance the drive to succeed and encourage students to participate in activities that help them realize their potential in achieving academic and personal success. The researchers aspires that this study will add to the understanding of how to support students in their psychological and social development to achieve optimal results in their academic and professional careers.